Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja Guru dan Mutu Pendidikan - Uuh Buchori; Umi Kultsum; Rodani (Akademika: Jurnal Manajemen Pendidikan Islam, 2022)
The main problem in this research is how is the leadership role of the school principal in improving teacher performance and quality of education at MAN 4 Pandeglang? This study aims to determine the leadership role of school principals in improving teacher performance and quality of education at MAN 4 Pandeglang. The method used in this study is a case study method, descriptive qualitative type through observation, interviews, and documentation, in an effort to describe the leadership role of the madrasa principal in improving the quality of education at MAN 4 Pandeglang, with resource persons from the madrasa principal, deputy head, teachers and student. The results of the research on the leadership role of school heads at MAN 4 Pandeglang are optimal. In carrying out his leadership, the head of the madrasa has a democratic nature in leading its members. In carrying out his leadership is quite wise and responsible. Teacher performance at MAN 4 Pandeglang has not been optimal. Although in terms of planning, until the evaluation at the end of the semester has been carried out, however, in terms of learning facilities and infrastructure, it is not sufficient to assist teachers in improving their performance, especially performance in the teaching and learning process. Regarding the quality of education at MAN 4 Pandeglang, it is good, and this is evidenced by the school accreditation score having point A, but it is necessary to increase the pedagogic competence of educators.